Investigating the effects of table movement and sag on optical surrogate-driven respiratory-guided computed tomography - Lackner, Niklas; Dietrich, Lou; Karius, Andre; Fietkau, Rainer; Bert, Christoph; Szkitsak, Juliane (Journal of Applied Clinical Medical Physics, 2024)
Purpose: Respiratory-guided computed tomography (CT) typically employs breathing motion surrogates to feed image reconstruction or visual breathing coaching. Our study aimed to assess the impact of table movements and table sag on the breathing curves recorded in four-dimensional (4D) CT and deep-inspiration breath-hold (DIBH) CT. Methods: For breathing curve measurements, static and dynamic phantom scenarios were used. Breathing curves were recorded using three different surrogate systems and the impact of table sag due to weights of up to 130 kg was analyzed and compared to a non-weighted setting, respectively. The calibration procedure of the system used as an input for the visual coaching device used for clinical DIBH CT scans was adapted. We evaluated corresponding breathing curves acquired during DIBH and 4DCT scans of altogether 70 patients using various stability metrics. Results: The various surrogate systems showed consistent table sag measurements below 4 mm, even under loads up to 130 kg, compared to a reference scan conducted without additional weight. Higher weight loads were related to steeper table sag fall-offs towards the deepest table position. For DIBH CT scans, the visual guidance was heavily affected by artifacts. This resulted in breathing threshold limits, which could not be achieved by 48% (n = 21) of the, respectively, examined patients. Using the new calibration workflow, the baseline drift was compensated better and 90% (n = 20) of the addressed patients stayed within the thresholds. The evaluated table sag in clinical 4DCT scans (n = 29) stayed below 3 mm compared to the non-weighted situation. Conclusion: Table movement and sag can impact breathing curves recorded by different surrogate systems. Correcting table movement and sag artifacts is crucial for reliable breathing curve acquisition in respiratory-guided CT.
CRIS-Team Scopus Importer:2024-12-13
Keywords: motion artifacts; respiratory motion; respiratory-guided CT; surrogate system; table sag

Noise reduction for single-shot grating-based phase-contrast imaging at an x-ray backlighter - Schreiner, Stephan; Akstaller, Bernhard; Dietrich, Lou; Meyer, Pascal; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Zielbauer, Bernhard; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2021)
X-ray backlighters allow the capture of sharp images of fast dynamic processes due to extremely short exposure times. Moiré imaging enables simultaneously measuring the absorption and differential phase-contrast (DPC) of these processes. Acquiring images with one single shot limits the X-ray photon flux, which can result in noisy images. Increasing the photon statistics by repeating the experiment to gain the same image is not possible if the investigated processes are dynamic and chaotic. Furthermore, to reconstruct the DPC and transmission image, an additional measurement captured in absence of the object is required. For these reference measurements, shot-to-shot fluctuations in X-ray spectra and a source position complicate the averaging of several reference images for noise reduction. Here, two approaches of processing multiple reference images in combination with one single object image are evaluated regarding the image quality. We found that with only five reference images, the contrast-to-noise ratio can be improved by approximately 13% in the DPC image. This promises improvements for short-exposure single-shot acquisitions of rapid processes, such as laser-produced plasma shock-waves in high-energy density experiments at backlighter X-ray sources such as the PHELIX high-power laser facility.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Grating-based phase-contrast; Image processing; Image quality improvement; Single-shot X-ray phase-contrast imaging; X-ray back-lighter; X-ray generators and sources

X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lou; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging